Initial experience and favorable outcomes on cannulation strategies and surgical platform construction in fully video-assisted thoracoscopic cardiac surgery - Liu, Zihou; Maimaitiaili, Abulizi; Ma, Xiaozhong; Dong, Shuangfeng; Wei, Wei; Wang, Qiang; Chen, Qingliang; Liu, Jianshi; Guo, Zhigang (Frontiers in Cardiovascular Medicine, 2024)
Background Minimally invasive cardiac surgery offers numerous advantages that patients and surgeons desire. This surgical platform encompasses cannulation strategies for cardiopulmonary bypass, optimal surgical access points, and high-quality visualization techniques. Traditional peripheral cannulation methods, though convenient, possess inherent limitations and carry the potential for complications such as retrograde dissection, stroke, or neurologic sequelae. Conversely, central cannulation may be ideally suited to circumvent the disadvantages above. Fully video-assisted thoracoscopy cardiac surgery represents a state-of-the-art platform, offering surgeons an unparalleled surgical view. This analysis aimed to delineate the efficacy and safety of transthoracic central cannulation strategies and the surgical platform during fully video-assisted thoracoscopy cardiac surgery. Methods Between October 2022 and February 2024, we identified a cohort of 85 consecutive patients with cardiopulmonary bypass undergoing fully video-assisted thoracoscopy cardiac surgery at our institutions. The patients' mean age was 41.09 ± 14.01 years, ranging from 18 to 75 years. The mean weight was 64.34 ± 10.59 kg (ranging from 49 to 103 kg). Congenital heart disease repair accounted for the highest proportion, with 43 cases (50.59%). Mitral valve surgery and left atrium Myxoma resections accounted for 29.41%. Specifically, this included 14 mitral valve repairs, five mitral valve replacements, and six left atrium myxoma resections. Aortic valve replacements constitute 20% of all cases. Results A total of 85 adult patients underwent fully video-assisted thoracoscopy cardiac surgery. The average CPB time was 83.26 ± 28.26 min, while the aortic cross-clamp time averaged 51.87 ± 23.91 min. The total operation time (skin to skin) averaged 173.8 ± 37.08 min. The mean duration of mechanical ventilation was 5.58 ± 3.43 h, ICU stay was 20.04 ± 2.83 h (ranging from 15.5 to 34 h), and postoperative hospital stay was 5.55 ± 0.87 days. No patients required conversion to thoracotomy and unplanned reoperations due to various reasons. There were no in-hospital deaths, strokes, myocardial infarctions, aortic dissections, or renal failure. No patient developed wound soft tissue infection. Conclusions Fully video-assisted thoracoscopy cardiac surgery utilizing central cannulation strategies is a reliable, cost-effective platform with a low risk of complications and a potential solution for patients facing contraindications for peripheral cannulation.